2013
DOI: 10.1038/nprot.2013.026
|View full text |Cite
|
Sign up to set email alerts
|

Surgical implantation of an abdominal imaging window for intravital microscopy

Abstract: High-resolution intravital microscopy through imaging windows has become an indispensable technique for the long-term visualization of dynamic processes in living animals. Easily accessible sites such as the skin, the breast and the skull can be imaged using various different imaging windows; however, long-term imaging studies on cellular processes in abdominal organs are more challenging. These processes include colonization of the liver by metastatic tumor cells and the development of an immune response in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
203
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(206 citation statements)
references
References 20 publications
3
203
0
Order By: Relevance
“…To perform intravital microscopy, human in vitro engineered organoids were infected (30) with pLKO-1.UbC.Dendra2.puro lentivirus. Ten to 12 wk after orthotopic organoid transplantation, an abdominal imaging window was surgically implanted on the primary tumor as described (12,31). The surgical procedure was performed under isoflurane inhalation anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…To perform intravital microscopy, human in vitro engineered organoids were infected (30) with pLKO-1.UbC.Dendra2.puro lentivirus. Ten to 12 wk after orthotopic organoid transplantation, an abdominal imaging window was surgically implanted on the primary tumor as described (12,31). The surgical procedure was performed under isoflurane inhalation anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…The techniques described here are also compatible with surgically placed window chambers 8,42,43 for longitudinal studies. The Procedure section consists of a step-by-step protocol for the study of nanoparticle transport and cell-particle interactions in the liver, followed by Application Notes section that describes how this protocol may be adapted for subcutaneous tumor imaging.…”
Section: Experimental Designmentioning
confidence: 95%
“…Repetitive imaging experiments are routinely performed in the brain by using an optical window, placed in an area of removed skull. Similar attempts to create windows in the abdomen have been attempted [13], but are not as yet widely used. However, a recent study has shown that repetitive kidney imaging can be performed by simply replacing the kidney back within the abdominal compartment after each experiment [14].…”
Section: Transgenic Animals Expressing Fluorescent Proteinsmentioning
confidence: 99%